Vegetation ecology of Central Europe. Volume II, coastal to alpine, natural to man-made habitats - Leuschner, Christoph; Ellenberg, Heinz, 1913- (Springer, 2017)
This is a comprehensive handbook in two volumes covering the heart of the continent, including Germany, Poland, the Netherlands, Belgium, Luxembourg, Switzerland, Austria, Czech Republic and Slovakia. Based on a thorough literature review with 5500 cited references and illustrated with nearly 1000 informative figures and tables, all vegetation types of this region are analysed in terms of their climatic and edaphic influences, the structure and dynamics of their communities, the ecophysiological constitution of the main plant species, important aspects of ecosystem functioning, and recent conservation issues. This volume deals with all types of non-forest vegetation in Central Europe, from the mostly natural coastal, mire, freshwater and alpine formations to the broad array of man-made habitats including managed grasslands, heathlands and arable fields, as well as ruderal and urban ecosystems. A key topic is human impact, which has influenced and shaped these ecosystems over the last 7000 years. The 14 chapters are arranged in a sequence from the natural non-forest formations to the purely anthropogenic ones, starting with coastal ecosystems (Chapters 1 and 2: salt marshes and dunes), followed by semi-aquatic ecosystems (Chapters 3 and 4: mires and freshwater systems) and alpine and nival ecosystems (Chapter 5). The subsequent group of anthropogenic systems starts with heathlands (Chapter 6) and managed dry or mesic to wet grasslands (Chapters 7 and 8) and proceeds to the vegetation of heavy metal-rich soils (Chapter 9), ruderal wet or mesic to dry habitats (Chapters 10 and 11), ending up with the heavily disturbed vegetation (Chapters 12 and 13: vegetation of arable land and urban areas). The summarising chapter (14) gives an overview of the most important plant communities of Central Europe.- Resumé vydavatel
Keywords: ekologie rostlin -- Evropa střední -- Alpy; ekologie lesa -- Evropa střední; plant ecology -- Europe, Central; forest ecology -- Europe, Central; elektronické knihy; electronic books